The effect of ethanolic extract of black and white rice bran (Oryza sativa L.) on cancer cells - Rizal Maarif Rukmana; Nyoman Puniawati Soesilo; Rumiyati Rumiyati; Rarastoeti Pratiwi (Universitas Gadjah Mada, 2016)
Indonesia has a wide range of rice cultivars and pigments. This rice can be used as a source of phytochemical compounds for cancer prevention. This research aims to analyze the cytotoxic activities of the ethanolic extract of black rice bran of 4 local cultivars i.e. ‘Cempo Ireng’, ‘Woja Laka’, ‘Toraja’ and ‘IR64’ (white rice) on cancer cells and to determine the compounds groups of those extracts. First step, rice bran was extracted with ethanol. This extract was applied to Raji (a human Burkitt Lymphoma cancer), HepG2 (a human liver cancer), and Vero (a nonhuman cell line) cells in order to measure the cytotoxic activities by using MTT assay. To determine descriptively the compounds groups of phenolics, flavonoids, terpenoids, steroids, and alkaloids the thin layer chromatography method was performed. The IC50 value was analyzed quantitatively by using probit analysis. Results showed that the IC50 values of ethanolic extract of rice bran ‘Woja Laka’, ‘Toraja’, ‘Cempo Ireng’ and ‘IR 64’ on HepG2 cells were 857.23±99.19; 1,896.55±83,8; 1,494.47±87.81 and 727.89±145,97 µg/ml respectively. The IC50 on Raji cells were 816.61±85.31; 1,079.93±28.31; 1,627.82; ±119.82, and 769.33±61.43 µg/ml respectively. The IC50 on Vero cells were 1,295.2±37; 1,232.07±165.51; 1,874.14±169.56, and 724.4±122.79 µg/ml respectively. The ethanolic extracts of rice bran from four cultivars contain phenolics, flavonoids, terpenoids, and steroids. However, alkaloids could not be detected. The variety of rice cultivars indicates the variation of cytotoxic activities on cancer cells. The ethanolic extracts of rice bran from those four rice cultivars contain similar kinds of organic compounds groups but vary in the Rf values.